Implementasi Peraturan Gubernur Provinsi Daerah Khusus Ibukota Jakarta Nomor 10 Tahun 2015 Tentang Penataan dan Pemberdayaan Pedagang Kaki Lima di Lokasi Sementara (LOKSEM) & Lokasi Binaan (LOKBIN) Kecamatan Tanah Abang - Luthfi Qilan Nurfarhan; Gunawan Djajaputra (LPPM Universitas Ekasakti Padang, 2023)
Street vendors are categorized as urban informal sectors that have not been accommodated in the official city plan, so it is not surprising that street vendors in the city or always become the main target of the city government to be put in order. But the fact is that various forms of policies in order to bring order to traders The street vendors that have been carried out by the city government have not run well in handling street vendors, it must be admitted that at this time there are regulations that will actually have an impact that is feared to decrease the income level of street vendors when compared to the location of origin because it is far from consumers or the target market of these street vendors. Based on the research background described above, I as a researcher decided to conduct research on the implementation of the Regulation of the Governor of the Special Capital Region of Jakarta Number 10 of 2015 concerning the Arrangement and Empowerment of Street Vendors in Temporary Locations & Assisted Locations Tanah Abang District.